Philanthropic Entrepreneurs Who Give Overseas: An Exploratory Study of International Giving Through Grassroots Organizations. (June 2020) - Appe, Susan; Oreg, Ayelet
We examine a phenomenon which includes people who have had transformative experiences while abroad and traveling, and who have returned home to the United States and become philanthropic entrepreneurs: they start their own international nonprofit organizations. We set out to examine the motivations for giving to international causes through these nonprofits, called grassroots, international non-governmental organizations (GINGOs), which allow individuals to actualize their calling to serve distant places and causes. As an exploratory, qualitative inquiry, we build on recent survey and experiment data about motivations to international giving and donor choice. In particular, GINGO leaders as philanthropic entrepreneurs challenge two main deterrents related to international giving: trust and its influence on willingness to donate to international causes and the adage that "charity begins at home." Our findings support suggestions in the literature that personal networks and word of mouth are important in donor choice and incentivizing giving to international causes.